2020
DOI: 10.1111/ctr.14074
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of renal transplantation in octogenarians

Abstract: With escalating life expectancy, elderly patients have become the fastest growing population initiating dialysis. Based on United States Renal Data System (USRDS) estimates, there are over 120 000 people in the United States with end-stage renal disease (ESRD) aged 75 years or older. 1 While this demographic only makes up 6.4% of the entire US population, it accounts for more than 16% of the ESRD population. 2 As elderly patients with kidney disease progress to ESRD and are initiated on dialysis, it is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This has resulted in an increase in number of kidney transplant referrals and surgeries for octogenarians 21. While overall post-transplant survival in very elderly kidney transplant recipients aged ≥80 has been reported to be lower than younger patients, studies have demonstrated that survival is still improved compared with remaining dialysis dependent 12 22. Octogenarians with ESKD experience a rapid loss of functional status and quality of life 23.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has resulted in an increase in number of kidney transplant referrals and surgeries for octogenarians 21. While overall post-transplant survival in very elderly kidney transplant recipients aged ≥80 has been reported to be lower than younger patients, studies have demonstrated that survival is still improved compared with remaining dialysis dependent 12 22. Octogenarians with ESKD experience a rapid loss of functional status and quality of life 23.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, very elderly patients with ESKD have high mortality with a median survival after dialysis initiation in the USA of 15.6 months for patients aged 80–84 and 11.6 months for patients aged 85–89 5. While several studies have demonstrated that kidney transplantation has excellent outcomes, including patient and graft survival, in carefully selected octogenarians,12 22 24 there have been concerns regarding increased perioperative mortality, length of hospital stay, rates of graft loss in very elderly kidney transplant recipients aged ≥80 as well as the need to balance recipient benefit with the ongoing organ shortage 25–28. A prior study of Organ Procurement and Transplantation Network (OPTN)/United Network for Organ Sharing database (UNOS) database of 471 octogenarians transplanted between 1988 and 2013 demonstrated increased risk of graft failure and decreased survival among this patient population 25.…”
Section: Introductionmentioning
confidence: 99%
“…A few recent European publications have suggested that recipients aged >65 years may not obtain a survival benefit from KT compared with remaining on dialysis [3,4]. In contrast, other studies have reinforced the benefit of transplantation among elderly candidates aged >60 years [10], 70–75 years [11,12], and even 80 years [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the cDCD‐KT results were not evaluated in these studies. Although most of the available evidence supports the practice of KT for elderly recipients [10–13], concerns have been raised about outcomes when using organs from cDCD donors in this population [3,4]. Thus, an analysis of the results is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, Zompolas et al conducted a retrospective study to evaluate outcomes of 85 kidney transplant recipients aged ≥ 75 years in the Eurotransplant Senior Program from January 2010 to July 2018 at the Charité-Universitätsmedizin Berlin in Germany [11]. The investigators demonstrated comparable outcomes among older patients compared to their younger counterparts [11], confirming excellent outcomes, including in patient and graft survival, in carefully selected older kidney transplant recipients aged ≥ 75 years [29][30][31]. Lastly, in this Special Issue, we reported outcomes of kidney transplant recipients with sickle cell disease (SCD) from an analysis of the 2000-2019 United Network for Organ Sharing (UNOS)/Organ Procurement and Transplantation Network Database [14].…”
mentioning
confidence: 95%